2007
DOI: 10.1002/vnl.20131
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of temperature on the leaching of organotin compounds from poly(vinyl chloride) plastics—A study conducted under simulated landfill conditions

Abstract: The aim of the study was to investigate whether organotin‐stabilized poly(vinyl chloride) (PVC) products could contribute to the pool of organotins observed in landfill leachates, and if the possible release could be related to different temperatures and landfill degradation phases. Small‐scale anaerobic reactors filled with generic household waste, a mixture of inocula, and different PVC plastics were used in the study and incubated at 20, 37, 55, and 70°C. The reactor units incubated at temperatures of 20–55… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Over the past few decades, various compounds have been studied as PVC stabilizers, such as metal soaps [7], lead salts [8], and organotin [9,10,11]. Although lead salts and organotin have been shown to be highly effective in stabilizing PVC, the properties of high toxicity for lead salts and high price for organotin limit their application [9,10,11]. On the other hand, metal soaps are also restricted because of their low workpiece ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, various compounds have been studied as PVC stabilizers, such as metal soaps [7], lead salts [8], and organotin [9,10,11]. Although lead salts and organotin have been shown to be highly effective in stabilizing PVC, the properties of high toxicity for lead salts and high price for organotin limit their application [9,10,11]. On the other hand, metal soaps are also restricted because of their low workpiece ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional, not biodegradable plastics, have shown meager degradation rates in simulated and real landfill conditions. This was found for PU [135], cellulose acetate [65], PP [136], and PVC [137]. Polyolefinic plastics (HDPE, LDPE, PP) and PS degraded between 4.96% and 15% in lysimeters that simulated landfill conditions [129].…”
Section: Anaerobic Digestionmentioning
confidence: 75%
“…More significantly, the environment of the plastics can affect chemical properties of polymers and their additives. For example, rising temperatures can promote movement of additives in polymers [115], and exposure to UV radiation can increase the rate of plastic degradation [116]. In addition, it has also been demonstrated that plastics that are exposed to the salinity of the water in the ocean can desorb estrogenic plasticizers [116].…”
Section: Health Impacts Of Plastic Additives Of Mnpsmentioning
confidence: 99%